PENGARUH RISIKO BANK TERHADAP EFISIENSI BANK SYARIAH - Intan Sukma Utami (Prosiding Seminar Nasional Indonesia, 2025)
Efficiency is one of the key indicators in assessing the performance of Islamic banking. One factor that potentially affects efficiency is bank risk, particularly financing risk as reflected in the Non-Performing Financing (NPF) ratio. This study aims to analyze the effect of bank risk on the efficiency of Islamic banks in Indonesia. The research employs panel data from 14 Islamic Commercial Banks over the period 2018–2024. The dependent variable is efficiency proxied by Return on Assets (ROA), while the independent variable is bank risk (NPF). The analysis was conducted using panel data regression with model selection tests, namely Chow, Hausman, and Lagrange Multiplier (LM), which indicated that the Random Effect Model (REM) was the most appropriate. The results reveal that bank risk (NPF) has no significant effect on the efficiency of Islamic banks. This finding indicates that although fluctuations in NPF occurred, the average remained below the 5% threshold set by Bank Indonesia, and thus was not sufficient to affect efficiency levels. This study implies the importance of managing financing risk to ensure that the efficiency of Islamic banks is maintained.